2013
DOI: 10.1039/c2an36450f
|View full text |Cite
|
Sign up to set email alerts
|

Forensic electrochemistry: sensing the molecule of murder atropine

Abstract: We present the electroanalytical sensing of atropine using disposable and economic screen printed graphite sensors. The electroanalytical determination of atropine is found to be possible over the concentration range of 5 μM to 50 μM with a detection limit of 3.9 μM (based on 3-sigma) found to be possible. We demonstrate proof-of-concept that this approach provides a rapid and inexpensive sensing strategy for determining the molecule of murder atropine in diet Coca-Cola samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 18 publications
1
52
2
1
Order By: Relevance
“…For example, Metters et al 6 have shown the constant diverse use of screen-printed sensors to many electrochemical targets, including chromium, 7 hydrazine 6 and atropine, 8 to name a few. Many researchers have expressed the need for miniaturisation of electrochemical setups and for the continuation of electroanalytical studies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Metters et al 6 have shown the constant diverse use of screen-printed sensors to many electrochemical targets, including chromium, 7 hydrazine 6 and atropine, 8 to name a few. Many researchers have expressed the need for miniaturisation of electrochemical setups and for the continuation of electroanalytical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Such analyses represent quite a challenge for the analyst due to low concentrations in biological samples as well as because of the presence of high levels of interfering compounds. [7][8][9] The above-mentioned methods usually involve time-consuming and multi-step pretreatment including liquid-liquid extraction and/or solid-phase extraction to remove impurities contained in plasma or serum for the detection of this species. 2 A high dosage of AT also stimulates the central nerve system.…”
Section: Introductionmentioning
confidence: 99%
“…Five street samples of NRG-2 were obtained from independent Internet vendors (January 2013), as off-white crystalline powders, in clear zip-lock bags. 13 For the fabrication of the screen-printed sensors, firstly, a carbon-graphite ink formulation (Gwent Electronic Materials Ltd, UK; product code: C2000802P2) was screen-printed onto a polyester (Autostat, 250 µm thickness) flexible film (denoted throughout as GSPEs). 3,15 The two flow cells used in this study were obtained from Metrohm UK, Runcorn, UK (impinging jet flow cell; product code: DRP-FLWCL-TEF-71306; 3.3 × 6.0 × 3.3 cm, flow chamber volume = 8 μL; denoted as FC-A, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 Since the legislative change, a number of evolved New Psychoactive Substance products, such as NRG-1 (naphyrone) and NRG-2 (Scheme 1), which are advertised to contain legal cathinone substitutes, have become widely available. 5,[8][9][10][11][12][13][14] Our previous work on the development of robust electrochemical methods for the sensing of the synthetic cathinones, mephedrone (2a) and 4-MEC (2b), either in their pure form 5 (LOD = 39.8-84.2 μg mL −1 ), using electroanalytical oxidation, or in the presence of common adulterants 15 (i.e. 3,4 Although many groups have reported analytical methods and structural data for many cathinone-derivatives, 3,5 including those found in samples of NRG-2, the prevalence of novel cathinones (especially 4-MMC 2,6 and 4-MEC 3,7 ) both as pure materials or within blended "legal high" products, continue to pose legal and analytical challenges in the rapid detection of these sub-stances by law enforcement, medical and customs officialsespecially as many of the current methods of field tests are unable to reliably discern individual components with a mixture of compounds.…”
Section: Introductionmentioning
confidence: 99%